The Effect Of Internship Experience, Soft Skills, And Social Support On Work Readiness Of Students Of The Faculty Of Economics And Business, State University Of Makassar With Learning Organization As An Intervening Variable - Ananda Putri; Syamsu Rijal; Muhammad Ilyas Thamrin Tahir; Inannah; Andi Annisa Sulolipu (Citakonsultindo, 2026)
The purpose of this study is to provide a comprehensive understanding of the influence of internship experience, social skills, and social support on the work readiness of economics students at Makassar State University, and Learning Organization as a mediating variable in the relationship between these variables. A quantitative approach was used in this study. Participants in this study consisted entirely of students of the Department of Economics, Makassar State University, and a sample of 271 students was identified using a purposive sampling technique. This data analysis was carried out using PLS-SEM. The results of the study found that internship experience, soft skills, and social support had a positive and significant effect on students' work readiness. Furthermore, learning organization was proven to act as a mediating variable that strengthens the relationship between students' internship experience, soft skills, social support, and work readiness. These findings indicate that improving the quality of internships, developing soft skill, and maximizing social support, supported by an effective learning organization environment, in its role to prepare students for professional and competitive performance in the workplace.